Disease-Associated Particulates and Joint Inflammation; Mechanistic Insights and Potential Therapeutic Targets - Mahon, Olwyn R.; Dunne, Aisling (Frontiers in Immunology, 2018)
It is now well established that intra-articular deposition of endogenous particulates, such as osteoarthritis-associated basic calcium phosphate crystals, gout-associated monosodium urate crystals and calcium deposition disease-associated CPP crystals, contributes to joint destruction through the production of cartilage-degrading enzymes and pro-inflammatory cytokines. Furthermore, exogenous wear debris particles, generated from prosthetic implants, drive periprosthetic osteolysis which impacts on the longevity of total joint replacements. Over the last few years, significant insight has been gained into the mechanisms through which these particulates exert their effects. Not only has this increased our understanding of the pathological processes associated with crystal deposition, it has also led to the identification of a number of therapeutic targets to treat particulate-associated disease. In this review, we discuss recent developments regarding the cellular events triggered by joint-associated particulates, as well as future directions in therapy for particulate related arthropathies.